Reassessing standardized tests: Evaluating their effectiveness in school performance measurement - Paramole, Oyeronke Christiana; Adeoye, Moses Adeleke (Curricula: Journal of Curriculum Development, 2024)
This research article reassesses the role of standardized tests in educational assessment, focusing on their complexities, historical context, and implications. It examines the accountability, and academic achievement benchmarks these tests provide while addressing criticisms such as cultural bias and narrowly teaching to the test. Alternative assessment methods, including formative and performance-based assessments, are also explored to offer a more holistic view of student learning and school performance. The article aims to contribute to a nuanced understanding of standardized tests' role in education, driving discussions on potential reforms that prioritize equitable and comprehensive assessment strategies. Critics raise concerns about the limitations of these tests, including their inability to capture the full range of student abilities, leading to biased and narrow educational outcomes. The study calls for a more balanced approach to educational assessment, integrating multiple methods to foster a more prosperous and fairer evaluation of student performance.